Performance and Gas Emissions Analysis on Four Stroke Diesel Engine with Multi-Feedstock Biodiesel - Sa'diyah, Aminatus; Ahmad Anda Aulatama; Hilmy Destiandi Ramadhan; Muchammad Nidhor Fairuza; Enggar Alfianto (Eksergi, 2024)
Biodiesel is one of the alternative fuels used in diesel engines. As the effectiveness of various biodiesel base materials varies, further studies on the effectiveness of biodiesel are needed. This study aims to evaluate the use of biodiesel from various sources as an alternative fuel. The methods in making multi-feedstock biodiesel are esterification and transesterification with palm oil, used cooking oil, and sunflower oil as raw materials. In this research, exhaust gas analysis and performance test on four stroke diesel engine were conducted. The mixture of biodiesel was then mixed with Pertamina Dex as High Speed Diesel (HSD) to produce B20, B35, and B100. The exhaust emission analysis focused on the concentration of (NOx) and (CO) gases at each rotation and load. The test result shows that B100 (100% multi-feedstock biodiesel) is the most optimal and environmentally friendly fuel with the same conditions of maximum load of 4000 watts and maximum rotation of 1400 rpm, NOx levels of 1396 mg/m3 and CO 474 ppm and has high power in all variations. On the other hand, HSD has the lowest gsfc in all variations.